2013
DOI: 10.1155/2013/416328
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Gel Treatments in Reservoirs with Multiscale Heterogeneity

Abstract: Spatially correlated permeability fields are usually generated by single-scale correlation. To overcome the limitations of single-scale permeability fields in describing real situation, permeability fields should be generated by multiscale correlation. Multiscale heterogeneity results in the existence of various permeability magnitudes and spatial distributions of permeability. Gel treatment is applied on the heterogeneous permeability fields realized by multiscale correlation. Performance of gel treatment has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For managing produced water, it is desirable to avoid production of water onto the surface in the first place. Among a variety of techniques, polymer-gel technology has been used for the problem of water production Bai et al, 2015b;Bailey et al, 2000;Bryant et al, 1996;El-Karsani et al, 2014;Hasankhani et al, 2019;Jia et al, 2012;Karimi et al, 2014;Lee and Lee, 2013;Nguyen et al, 2012;Reddy et al, 2003;Seright, 1992Seright, , 1995Seright and Martin, 1993;Zitha et al, 2002). In this method, the polymer-gel solution is injected into the oil/gas wells to selectively block the water's path to the wellbore, and consequently to improve the conformance while minimizing the adverse effects of reservoir heterogeneity during waterflooding operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For managing produced water, it is desirable to avoid production of water onto the surface in the first place. Among a variety of techniques, polymer-gel technology has been used for the problem of water production Bai et al, 2015b;Bailey et al, 2000;Bryant et al, 1996;El-Karsani et al, 2014;Hasankhani et al, 2019;Jia et al, 2012;Karimi et al, 2014;Lee and Lee, 2013;Nguyen et al, 2012;Reddy et al, 2003;Seright, 1992Seright, , 1995Seright and Martin, 1993;Zitha et al, 2002). In this method, the polymer-gel solution is injected into the oil/gas wells to selectively block the water's path to the wellbore, and consequently to improve the conformance while minimizing the adverse effects of reservoir heterogeneity during waterflooding operations.…”
Section: Introductionmentioning
confidence: 99%
“…Most hydrocarbon reservoirs show complex geological heterogeneity due to the presence of rocks with a wide range of pore and grain sizes, different physical properties including permeability in particular, and the presence of natural features such as fractures. Reservoir heterogeneity, e.g., spatial variations in permeability, has been known as one of the reasons for low recovery of oil and early water production (Amir et al, 2019;Hasankhani et al, 2018;Heidari et al, 2018;Lee and Lee, 2013). As heterogeneity in permeability increases, flow paths become more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…This parameter has been studied for dispersion in porous media [6], recovery of oil reservoirs [7][8][9] and CO 2 storage in aquifers [10]. Other static measures included Lorenz coefficient [11], heterogeneity factor [12], sand index [13], coefficient of variation [14], standard deviation and correlation length [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al [19] presented the results of an experimental study of pressuredependent natural-fracture permeability in SGR and found that the effect of pressure-dependent natural-fracture permeability on shale gas well production was a function of the permeability of the matrix system. J. H. Lee and K. S. Lee [20] studied the multiscale heterogeneity in the existence of various permeability magnitudes and spatial distributions of permeability. Du et al [21] presented a new experimental method explaining the flooding tests in the low-permeability reservoirs.…”
Section: Introductionmentioning
confidence: 99%